Pneumocystis and Severe Acute Respiratory Syndrome Coronavirus 2 Coinfection: A Case Report and Review of an Emerging Diagnostic Dilemma. (18th December 2020) - Rubiano, Carlos; Tompkins, Kathleen; Sellers, Subhashini A; Bramson, Brian; Eron, Joseph; Parr, Jonathan B; Schranz, Asher J
Abstract: We present a case of a critically ill patient with coronavirus disease 2019 (COVID-19) found to have acquired immune deficiency syndrome and Pneumocystis jirovecii pneumonia (PCP). Coronavirus disease 2019 and PCP co-occurrence is increasingly reported and may complicate diagnostic and therapeutic strategies. Patients with severe COVID-19 should be screened for underlying immunocompromise and coinfections should be considered.